Peningkatan Hasil Belajar Siswa Melalui Metode SYTEAMAMA pada SMA Negeri 1 Suliki Kabupaten Limapuluh Kota - NURLAILA, NURLAILA (TINGKAP, 2012)
This action research aimed to increase learning achievement of students on Civic Education at grade XII SMA Negeri 1 Suliki, the District of Limapuluh Kota, through the implementation of Syteamama method. This study was conducted through an action research with two learning cycles and four steps for each step as suggested by Kemmis dan Taggart, that is planning, action, observation, and reflection. The finding of this study generally indicated that implementation Syteamama method could increase the learning achievement of students on civic education significantly, especially at grade XII SMA Negeri 1 Suliki, the District of Limapuluh Kota. Kata Kunci: hasil belajar, metode Syteamama, Pendidikan Kewar-ganegaraan